Calcified neck tumor - Pomi, Jorge; Balboa, Oscar (Cirugía del Uruguay, 1978)
The paper refers to the case of a 63-year-old patient suffering from multinodular goiter which extended onto the thorax. One of its cervical nodes presented peripheral calcification in the form of a halo, a characteristic which renders it unusual.